Lisfranc Injury in Adolescents - Veijola, Kia; Laine, Heikki-Jussi; Pajulo, Olli (European Journal of Pediatric Surgery, 2013)
Background There are only few studies of Lisfranc injuries in children and adolescents. The aim of this study was to evaluate the mid-term results of the operatively treated injuries.Methods Seven Lisfranc injuries of adolescents were treated operatively in the Tampere University Hospital between 2004 and 2009. In four of the seven feet, the trauma comprised all the metatarsal bones. All patients were treated with open reduction and internal fixation. A questionnaire concerning the function and pain of the foot was sent to all the patients.Results In all but one case, the anatomical reduction was achieved and held during the follow-up. However, most patients claimed discomfort or constant harm in the injured foot at the end of the follow-up. Still, all the patients were able to run and no one needed to wear special shoes or any other kind of means.Conclusions Lisfranc injuries in adolescents are likely to cause constant harm, even if the anatomical reduction is achieved.
Keywords: foot injuries; dislocations; adolescents; metatarsal bones